Biodegradable composites : materials, manufacturing and engineering - Kumar, K. 1968-; Davim, J. Paulo (Advanced composites., 2019)
Composite materials are engineered materials, made from two or more constituents with significantly different physical or chemical properties which remain separate on a macroscopic level within the finished structure. Due to their special mechanical and physical properties they have the potential to replace conventional materials.- Resumé vydavatel